FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH BERBASIS MASYARAKAT PADA DINAS KEBERSIHAN DAN PERTAMANAN KOTA SEMARANG (SOLUSI PENGURANGAN TIMBUNAN SAMPAH DI TPA JATI BARANG) - Hree Galung Wisesa; Zaenal Hidayat; Nina Widowati (Journal of Public Policy and Management Review, 2013)
Community based solid waste management program is an effort that is used by the central and local governments. While the department of cleaning and parks Semarang to tackle a pile of garbage and landfill almost overload teak semarang goods, it has another purpose is to empower people to do the trash with the 3R / 3M.Waste management Semarang current applied to create community-based waste management system consisting of a waste management and waste banks aimed at reducing the volume of waste going into landfill Teak Goods.If there are obstacles and support the task of the government and all actors contained in this community-based waste management can better utilize the support to cover the obstacles that occur.